Theophany and Parousia - Glasson, T. Francis (New Testament studies, 1988)
The importance of the OT theophanies in relation to NT conceptions of the End has never been sufficiently realized. Again and again the prophets and psalmists spoke not merely of the Day of the Lord but they spelled this out in terms of a divine coming. Thus in Mic 1. 3 we read that ‘the Lord cometh forth out of his place, and will come down …’ Psa 96. 13 declares, ‘He cometh to judge the earth.’